Psychological Value Analysis in the Novel Our Home by Valentina Madihanto - Wonmaly, Windy; Jaftoran, Jesinta; Laurens, Paskah; Luanmasar, Bahtera Lulusiaman (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study aims to describe the psychological values found in the novel Our Home by Valentina Madihanto (2024). The study applies a literary psychology approach using Sigmund Freud’s psychoanalytic theory, which includes the Id, Ego, and Superego, to analyze the inner conflicts of the characters. This research employs a descriptive qualitative method. The data consist of quotations from the novel that reflect psychological values. The data were collected through reading and note-taking techniques, while the analysis was conducted by identifying, classifying, and interpreting the data based on Freud’s psychoanalytic theory.The results show that the dominant psychological values in the novel include fear, anxiety, trauma, anger, emotional pressure, feelings of worthlessness, and lack of affection within the family. The absence of parental attention and warmth becomes the main factor causing the characters’ inner conflicts. These conflicts arise from the tension between the Id as instinctual drives, the Ego as a mediator of reality, and the Superego as moral control, which results in emotional distress affecting the characters’ personality development. Thus, the novel Our Home not only portrays family conflicts but also highlights the impact of lack of affection on children’s psychological condition and personality formation.